Presence of both mating types of Ascochyta rabiei in Argentina suggests potential for sexual reproduction - Crociara, Clara Sonia; Valetti, Lucio; Pastor, Silvina Estela (Springer, 2021)
The presence of both mating types was tested for in twelve isolates of Ascochyta rabiei in Argentina. A MATspecific PCR assay was performed. Nine of these isolates were identified as MAT1–1 and three of them MAT1–2. This is the first research regarding the mating types of Ascochyta rabiei in the country and suggests that there is a potential for sexual reproduction in Argentina.